Single crystal diamond composite material and preparation method and application thereof, and cobalt-based ceramic composite material and preparation method and application thereof

By covering the functional layers of materials such as TiC, ZrH2 and Al on the surface of single crystal diamond, the problem of diamond carbonization in traditional cermet materials during sintering is solved, and the hardness and wear resistance of the material are significantly improved.

CN119530625AActive Publication Date: 2025-02-28JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510095867.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-02-28
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Traditional cermet materials are prone to carbonization of diamond during sintering, affecting their hardness and wear resistance.

Method used

A single crystal diamond composite material is used, which consists of single crystal diamond and a functional layer coated on the surface of the single crystal diamond. The materials of the functional layer include TiC, ZrH2 and Al. These components are evenly mixed by ball mill mixing technology to form a dense composite material to avoid diamond carbonization at high temperatures.

Benefits of technology

Effectively prevent diamond from carbonizing at high temperatures, improve the hardness and wear resistance of metal cermet materials, and extend the service life of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530625A_ABST
    Figure CN119530625A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramic materials, and particularly relates to a monocrystal diamond composite material and a preparation method and application thereof, and a cobalt-based ceramic composite material and a preparation method and application thereof. The monocrystal diamond composite material provided by the invention comprises monocrystal diamond and a functional layer coated on the surface of the monocrystal diamond, and the material of the functional layer comprises TiC, ZrH2 and Al. Through coating of the functional layer, a protective layer is formed on the surface of the diamond, so that the diamond is not influenced by high temperature during sintering, the phenomenon of high-temperature carbonization in the discharge sintering process is effectively avoided, and the hardness and wear resistance of the diamond are kept; zrH2 is decomposed to release hydrogen in the sintering process, air holes in the material are effectively removed, densification of the material is promoted, meanwhile, the binding force between the diamond and the metal matrix is enhanced, good interface bonding can be formed between the diamond and the metal matrix, and therefore the mechanical property and abrasion resistance of the composite material are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic materials, and in particular relates to a single crystal diamond composite material and a preparation method and application thereof, and a cobalt-based ceramic composite material and a preparation method and application thereof. Background Art

[0002] Metal-ceramic materials are composed of a hard phase with high hardness and high melting point and a bonding phase with high toughness and relatively low melting point. Among them, metal bonding phase cemented carbides based on Co, Ni and Fe have been widely used in industry. Co has excellent wettability to WC and also has superior mechanical properties, making Co the most widely used metal in the bonding phase. Diamond, as the hardest substance in nature, has extremely high hardness and wear resistance. Introducing it into metal-ceramic materials can significantly improve the hardness and wear resistance of the composite material. This enhancement effect mainly comes from the uniform distribution of diamond particles in the composite material, which can effectively resist external loads and friction, thereby extending the service life of the material.

[0003] The traditional method for preparing metal ceramic materials is mainly the spark plasma sintering process. During the sintering process, when discharge occurs in the gaps between the grains, local high temperatures of up to several thousand to ten thousand degrees will be generated. The formation of local high temperatures can easily lead to carbonization of the diamond surface, thereby affecting the hardness and wear resistance of the cemented carbide. Summary of the invention

[0004] The purpose of the present invention is to provide a single crystal diamond composite material and a preparation method and application thereof, a cobalt-based ceramic composite material and a preparation method and application thereof. The single crystal diamond composite material provided by the present invention can effectively prevent diamond from being carbonized at high temperatures, and can be applied to metal ceramic materials to further improve their hardness and wear resistance.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a single crystal diamond composite material, comprising a single crystal diamond and a functional layer coated on the surface of the single crystal diamond; The material of the functional layer includes TiC, ZrH 2 and Al.

[0006] Preferably, the single crystal diamond composite material comprises the following components in percentage by weight: 50-60% single crystal diamond, 20-30% TiC, 5-15% ZrH 2 and 5-15% Al; The particle size of the single crystal diamond is 100-200 μm; the particle size of the TiC is 0.5-10 μm; the ZrH 2The particle size of the Al is 48~75μm.

[0007] The present invention also provides a method for preparing the single crystal diamond composite material described in the above technical solution, comprising the following steps: The components included in the single crystal diamond composite material are ball-milled and mixed to obtain the single crystal diamond composite material.

[0008] Preferably, the ball milling mixing is performed at a rotation speed of 80-100 rpm for 48 hours.

[0009] The present invention also provides the use of the single crystal diamond composite material described in the above technical solution or the single crystal diamond composite material prepared by the preparation method described in the above technical solution in metal-ceramic composite materials.

[0010] The present invention also provides a cobalt-based ceramic composite material, comprising the following raw materials in percentage by weight: WC70-80%, Co 10-25%, Yb 2 O 3 0~2% and the balance of modified diamond; The modified diamond is the single crystal diamond composite material described in the above technical solution or the single crystal diamond composite material prepared by the preparation method described in the above technical solution.

[0011] Preferably, the particle size of the WC is 0.5-75 μm; The particle size of the Co is 48-75 μm; The Yb 2 O 3 The particle size is 48~75μm.

[0012] The present invention also provides a method for preparing the cobalt-based ceramic composite material described in the above technical solution, comprising the following steps: Ball-milling and mixing the raw materials for preparing the cobalt-based ceramic composite material to obtain a mixed material; The mixed material is sintered to obtain the cobalt-based ceramic composite material.

[0013] Preferably, the ball milling mixing is performed at a speed of 160-180 rpm for 48 hours; The sintering includes sequentially performing a first sintering, a second sintering and a third sintering; The first sintering temperature is 550-650°C, the holding time is 2-3 minutes, and the pressure is 12-15 kN; The second sintering temperature is 850-950°C, the holding time is 2-3 minutes, and the pressure is 23-25 ​​kN; The third sintering temperature is 1340-1360° C., the holding time is 0-6 min, and the pressure is 30-33 kN; The sintering is carried out under vacuum conditions, with a vacuum degree of ≤8×10 0 Pa.

[0014] The present invention also provides the use of the cobalt-based ceramic composite material described in the above technical solution or the cobalt-based ceramic composite material prepared by the preparation method described in the above technical solution as a cutting tool.

[0015] The present invention provides a single crystal diamond composite material, comprising a single crystal diamond and a functional layer coated on the surface of the single crystal diamond; the material of the functional layer comprises TiC, ZrH 2 and Al.

[0016] In the present invention, by adding TiC, the wettability of the functional layer to diamond can be further improved, and the holding force of the bonding phase matrix to diamond can be improved; wherein ZrH 2 During the sintering process, it decomposes and releases hydrogen, effectively removes pores in the material, promotes material densification, and at the same time enhances the bonding force between diamond and metal matrix, so that a good interface bonding can be formed between diamond and metal matrix, thereby further improving the wear resistance, bending strength and impact toughness of the alloy structure; the addition of aluminum can improve the effect of diamond wrapping, improve the bonding relative to diamond, and the low melting point of aluminum can improve the density of the alloy structure by using its filling effect, while inhibiting the growth of WC grains and having the effect of refining grains. In the present invention, a protective layer is formed on the surface of the diamond by coating with a functional layer, so that it is not affected by high temperature during sintering, effectively avoiding the occurrence of high temperature carbonization during discharge sintering, thereby maintaining its hardness and wear resistance.

[0017] The present invention also provides a cobalt-based ceramic composite material, comprising the following raw materials in percentage by weight: WC70-80%, Co 10-25%, Yb 2 O 3 0~2% and modified diamond; the modified diamond is the single crystal diamond composite material described in the above technical solution or the single crystal diamond composite material prepared by the preparation method described in the above technical solution. In the present invention, in the specific sintering process, a new phase of tungsten carbide aluminum (W-Al-C) can be formed. The formation of this new phase greatly improves the hardness and wear resistance of the composite material, so that the material exhibits better mechanical properties under high temperature and high stress environment, can effectively resist external loads and friction, and prolong service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM image of the cobalt-based ceramic composite material obtained in Example 1 with a scale of 50 μm; Figure 2 This is a SEM image of the cobalt-based ceramic composite material obtained in Example 1 with a scale of 200 μm; Figure 3 This is a SEM image of the cobalt-based ceramic composite material obtained in Example 1 with a scale of 1 mm; Figure 4 This is a SEM image of the cobalt-based ceramic composite material obtained in Example 1 with a scale of 100 μm; Figure 5 This is the EDS spectrum of the cobalt-based ceramic composite material obtained in Example 1; Figure 6 This is a SEM image of the cobalt-based ceramic composite material obtained in Example 2 with a scale of 100 μm; Figure 7 This is a SEM image of the cobalt-based ceramic composite material obtained in Example 2 with a scale of 20 μm; Figure 8 is the XRD pattern of the cobalt-based ceramic composite material obtained in Example 4; Fig. 9 This is a SEM image of the cobalt-based ceramic composite material obtained in Comparative Example 1; Fig.10 This is a SEM image of the cobalt-based ceramic composite material obtained in Comparative Example 1; Fig.11 This is a three-dimensional profile diagram of the cobalt-based ceramic composite material obtained in Example 1 after the friction and wear test; Fig.12 This is a three-dimensional profile diagram of the cobalt-based ceramic composite material obtained in Example 1 after the friction and wear test; Fig.13 This is the electrochemical polarization curve of the cobalt-based ceramic composite material obtained in Example 1. DETAILED DESCRIPTION

[0019] The present invention provides a single crystal diamond composite material, comprising a single crystal diamond and a functional layer coated on the surface of the single crystal diamond; The material of the functional layer includes TiC, ZrH 2 and Al.

[0020] In the present invention, the single crystal diamond composite material preferably comprises the following components in percentage by mass: 50-60% single crystal diamond, 20-30% TiC, 5-15% ZrH 2 And 5~15%Al.

[0021] In terms of mass percentage, the single crystal diamond composite material provided by the present invention preferably includes 50-60% single crystal diamond, specifically 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%. In the present invention, the particle size of the single crystal diamond is preferably 100-200 μm.

[0022] In terms of mass percentage, the single crystal diamond composite material provided by the present invention preferably includes 20-30% TiC, specifically 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%. In the present invention, the particle size of the TiC is preferably 0.5-10 μm.

[0023] In terms of mass percentage, the single crystal diamond composite material provided by the present invention preferably comprises 5-15% ZrH 2 , specifically 5%, 10%, and 15%. In the present invention, the ZrH 2 The particle size is preferably 48 to 75 μm.

[0024] In terms of mass percentage, the single crystal diamond composite material provided by the present invention preferably includes 5-15% Al, specifically 5%, 10%, 15%. In the present invention, the particle size of the Al is preferably 48-75 μm.

[0025] The present invention also provides a method for preparing the single crystal diamond composite material described in the above technical solution, comprising the following steps: The components included in the single crystal diamond composite material are ball-milled and mixed to obtain the single crystal diamond composite material.

[0026] Before the ball milling and mixing, the present invention also preferably includes cleaning the single crystal diamond. The cleaning method is preferably ultrasonic cleaning with anhydrous ethanol. Ultrasonic cleaning can remove pollutants on the surface of the single crystal diamond, so that the diamond surface can be completely and truly separated from TiC, ZrH 2 , Al to make the bonding strength of the wrapped diamond more superior.

[0027] In the present invention, the rotation speed of the ball milling is preferably 80-100 rpm, and the time is preferably 48 hours. In the present invention, the ball milling is preferably carried out in a planetary ball mill, the tank of the planetary ball mill is preferably a vacuum ceramic tank, and the grinding balls used are preferably ceramic balls. In the present invention, the use of a vacuum ceramic tank and ceramic balls for ball milling can prevent Al from being oxidized during the ball milling process.

[0028] The present invention also provides the use of the single crystal diamond composite material described in the above technical solution or the single crystal diamond composite material prepared by the preparation method described in the above technical solution in metal-ceramic composite materials.

[0029] The present invention also provides a cobalt-based ceramic composite material, comprising the following raw materials in percentage by weight: WC70-80%, Co 10-25%, Yb 2 O 3 0~2% and modified diamond; The modified diamond is the single crystal diamond composite material described in the above technical solution or the single crystal diamond composite material prepared by the preparation method described in the above technical solution.

[0030] In terms of mass percentage, the raw material for preparing the cobalt-based ceramic composite material provided by the present invention includes WC 70-80%, specifically 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%. In the present invention, the particle size of the WC is preferably 0.5-75 μm, specifically 0.5-1 μm or 48-75 μm.

[0031] In terms of mass percentage, the raw material for preparing the cobalt-based ceramic composite material provided by the present invention includes Co 10-25%, specifically 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%. In the present invention, the particle size of the Co is preferably 48-75 μm.

[0032] In terms of mass percentage, the raw materials for preparing the cobalt-based ceramic composite material provided by the present invention include Yb 2 O 3 0~2%, specifically 0% (i.e. no Yb added 2 O 3 ), 1%, 2%. In the present invention, the Yb 2 O 3 The particle size is preferably 48 to 75 μm. In the present invention, by adding Yb 2 O 3 It can enhance the organizational properties and further strengthen the holding power of diamond and matrix organization.

[0033] The present invention also provides a method for preparing the cobalt-based ceramic composite material described in the above technical solution, comprising the following steps: Ball-milling and mixing the raw materials for preparing the cobalt-based ceramic composite material to obtain a mixed material; The mixed material is sintered to obtain the cobalt-based ceramic composite material.

[0034] In the present invention, the rotation speed of the ball milling is preferably 160-180 rpm, and the time is preferably 48 hours. In the present invention, the ball milling is preferably carried out in a planetary ball mill, the tank of the planetary ball mill is preferably a vacuum stainless steel tank, and the grinding balls used are preferably stainless steel balls; the use of a vacuum stainless steel tank and stainless steel balls for ball milling in the present invention can further ensure that the raw materials are mixed evenly.

[0035] In the present invention, the sintering preferably includes the first sintering, the second sintering and the third sintering in sequence; the temperature of the first sintering is preferably 550~650℃, specifically 550℃, 600℃, 650℃, the holding time is preferably 2~3min, and the pressure is preferably 12~15kN; the temperature of the second sintering is preferably 850~950℃, specifically 850℃, 900℃, 950℃, the holding time is preferably 2~3min, and the pressure is preferably 23~25kN; the temperature of the third sintering is preferably 1340~1360℃, the holding time is preferably 0~6min, and the pressure is preferably 30~33kN; the heating rate during the first sintering, the second sintering and the third sintering is independently preferably 80~100℃ / min. In the present invention, the sintering method is preferably spark plasma sintering. In the present invention, the sintering is preferably carried out under vacuum conditions, and the vacuum degree is ≤8×10 0 Pa. In the present invention, the sintering is preferably carried out in a sintering furnace, the pulse ratio of the sintering furnace is preferably 14, and the heating voltage is preferably 5-6V.

[0036] In the present invention, ZrH 2 It decomposes at high temperatures and releases hydrogen, which effectively reduces the porosity during sintering, increases the density of the material, and reduces the generation of cracks. 2 It can also enhance the wettability of the bonding phase to diamond, form a high-strength chemical bond between the coating and the diamond, and promote the uniform dispersion of diamond particles in the alloy matrix, thereby further improving the mechanical properties and wear resistance of the material and realizing the efficient application of diamond in tungsten-cobalt alloys. 2 O 3 The addition of also promotes the fluidity of WC and Co, and improves the overall density and structural strength of the composite material.

[0037] In the present invention, the eutectic temperature of WC-Co is 1340°C, the sintering temperature is close to the eutectic temperature, and WC diffuses and dissolves in Co to produce a liquid phase. The sintering temperature is slightly higher than the eutectic temperature, and combined with the rapid cooling process, the grain growth is effectively inhibited to form a denser organizational structure. In addition, during the sintering process, due to the interaction of elements such as tungsten and aluminum, a new phase of tungsten carbide aluminum (W-Al-C) is generated. The formation of this new phase not only improves the hardness of the material, but also enhances its wear resistance and high temperature stability.

[0038] The present invention also provides the use of the cobalt-based ceramic composite material described in the above technical solution or the cobalt-based ceramic composite material prepared by the preparation method described in the above technical solution as a cutting tool.

[0039] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0040] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Example 1 The single crystal diamond is ultrasonically cleaned with anhydrous ethanol to remove and disperse the surface dirt to achieve the cleaning purpose, and then dried for use; Preparation of single crystal diamond composite material: 55% cleaned single crystal diamond, 25% TiC, 10% ZrH 2 and 10% Al were uniformly mixed using a planetary ball mill; the particle size of the single crystal diamond was 180 μm, the particle size of TiC was 10 μm, and the particle size of ZrH 2 The particle size of the raw materials is 48 μm, and the particle size of the Al is 48 μm. The ball milling is carried out using a vacuum ceramic jar and ceramic balls, the ball milling speed is 80 rpm, the ball milling time is 48 h, and after uniform mixing, a single crystal diamond composite material is obtained, which is vacuum sealed for standby use. Preparation of cobalt-based ceramic composites: 5% single crystal diamond composite material, 80% WC, 13% Co and 2% Yb 2 O 3 A planetary ball mill was used for uniform mixing, wherein the particle size of WC powder was 0.5 μm, the particle size of Co was 48 μm, and the particle size of Yb was 1.3 μm. 2 O 3 The particle size is 48 μm; the ball milling is carried out using a stainless steel tank and stainless steel balls, the ball milling speed is 180 rpm, and the ball milling time is 48 hours to obtain a mixture; The mixed material obtained above was evenly spread in a cylindrical graphite mold, placed in a sintering furnace, and the process parameters were adjusted to perform the first sintering, the second sintering and the third sintering in sequence to obtain a cobalt-based ceramic composite material; wherein the sintering parameters were as follows: the pressure of the first sintering was 13 kN, the heating rate was 100 °C / min, the temperature reached 600 °C, and the holding time was 2 min; the pressure of the second sintering was 25 kN, the heating rate was 100 °C / min, the temperature reached 900 °C, and the holding time was 2 min; the pressure of the third sintering was 30 kN, the heating rate was 100 °C / min, the temperature reached 1360 °C, and the holding time was 6 min, and the vacuum degree was controlled to be ≤8×10 0 Pa, the pulse ratio of the sintering furnace is 14, and the heating voltage is 5~6V.

[0042] Example 2 The single crystal diamond is ultrasonically cleaned with anhydrous ethanol to remove and disperse the surface dirt to achieve the cleaning purpose, and then dried for use; Preparation of single crystal diamond composite material: 55% cleaned single crystal diamond, 25% TiC, 10% ZrH 2 and 10% Al were uniformly mixed using a planetary ball mill; the particle size of the single crystal diamond was 180 μm, the particle size of TiC was 10 μm, and the particle size of ZrH 2 The particle size of the raw materials is 48 μm, and the particle size of the Al is 48 μm. The ball milling is carried out using a vacuum ceramic jar and ceramic balls, the ball milling speed is 80 rpm, the ball milling time is 48 h, and after uniform mixing, a single crystal diamond composite material is obtained, which is vacuum sealed for standby use. Preparation of cobalt-based ceramic composite materials: 5% of single crystal diamond composite materials, 75% of WC and 20% of Co were uniformly mixed by a planetary ball mill, wherein the particle size of WC powder was 48 μm, and the particle size of Co was 48 μm; the ball milling was carried out by using a vacuum stainless steel tank and stainless steel balls; the ball milling speed was 180 rpm, and the ball milling time was 48 h to obtain a mixture; The mixed material obtained above was evenly spread in a cylindrical graphite mold, placed in a sintering furnace, and the process parameters were adjusted to perform the first sintering, the second sintering and the third sintering in sequence to obtain a cobalt-based ceramic composite material; wherein the sintering parameters were as follows: the pressure of the first sintering was 13 kN, the heating rate was 100 °C / min, the temperature reached 600 °C, and the holding time was 2 min; the pressure of the second sintering was 25 kN, the heating rate was 100 °C / min, the temperature reached 900 °C, and the holding time was 2 min; the pressure of the third sintering was 30 kN, the heating rate was 100 °C / min, the temperature reached 1360 °C, and the holding time was 3 min, and the vacuum degree was controlled to be ≤8×10 0 Pa, the pulse ratio of the sintering furnace is 14, and the heating voltage is 5~6V.

[0043] Example 3 The single crystal diamond is ultrasonically cleaned with anhydrous ethanol to remove and disperse the surface dirt to achieve the cleaning purpose, and then dried for use; Preparation of single crystal diamond composite material: 50% cleaned single crystal diamond, 30% TiC, 10% ZrH 2 and 10% Al were uniformly mixed using a planetary ball mill; the particle size of the single crystal diamond was 180 μm, the particle size of TiC was 10 μm, and the particle size of ZrH 2 The particle size of the raw materials is 48 μm, and the particle size of the Al is 48 μm. The ball milling is carried out using a vacuum ceramic jar and ceramic balls, the ball milling speed is 80 rpm, the ball milling time is 48 h, and after uniform mixing, a single crystal diamond composite material is obtained, which is vacuum sealed for standby use. Preparation of cobalt-based ceramic composite materials: 5% of single crystal diamond composite materials, 70% of WC and 25% of Co were uniformly mixed by a planetary ball mill, wherein the particle size of WC powder was 48 μm, and the particle size of Co was 48 μm; the ball milling was carried out by using a vacuum stainless steel tank and stainless steel balls; the ball milling speed was 180 rpm, and the ball milling time was 48 h to obtain a mixture; The mixed material obtained above was evenly spread in a cylindrical graphite mold, placed in a sintering furnace, and the process parameters were adjusted to perform the first sintering, the second sintering and the third sintering in sequence to obtain a cobalt-based ceramic composite material; wherein the sintering parameters were as follows: the pressure of the first sintering was 12 kN, the heating rate was 80 °C / min, the temperature reached 600 °C, and the holding time was 2 min; the pressure of the second sintering was 23 kN, the heating rate was 80 °C / min, the temperature reached 900 °C, and the holding time was 2 min; the pressure of the third sintering was 30 kN, the heating rate was 80 °C / min, the temperature reached 1360 °C, and the holding time was 0 min, and the vacuum degree was controlled to be ≤8×10 0 Pa, the pulse ratio of the sintering furnace is 14, and the heating voltage is 5~6V.

[0044] Example 4 The single crystal diamond is ultrasonically cleaned with anhydrous ethanol to remove and disperse the surface dirt to achieve the cleaning purpose, and then dried for use; Preparation of single crystal diamond composite material: 55% cleaned single crystal diamond, 25% TiC, 10% ZrH 2 and 10% Al were uniformly mixed using a planetary ball mill; the particle size of the single crystal diamond was 180 μm, the particle size of TiC was 10 μm, and the particle size of ZrH 2The particle size of the raw materials is 48 μm, and the particle size of the Al is 48 μm. The ball milling is carried out using a vacuum ceramic jar and ceramic balls, the ball milling speed is 80 rpm, the ball milling time is 48 h, and after uniform mixing, a single crystal diamond composite material is obtained, which is vacuum sealed for standby use. Preparation of cobalt-based ceramic composite materials: 5% of single crystal diamond composite materials, 75% of WC and 20% of Co were uniformly mixed by a planetary ball mill, wherein the particle size of WC powder was 48 μm, and the particle size of Co was 48 μm; the ball milling was carried out by using a vacuum stainless steel tank and stainless steel balls; the ball milling speed was 180 rpm, and the ball milling time was 48 h to obtain a mixture; The mixed material obtained above was evenly spread in a cylindrical graphite mold, placed in a sintering furnace, and the process parameters were adjusted to perform the first sintering, the second sintering and the third sintering in sequence to obtain a cobalt-based ceramic composite material; wherein the sintering parameters were as follows: the pressure of the first sintering was 13 kN, the heating rate was 100 °C / min, the temperature reached 600 °C, and the holding time was 2 min; the pressure of the second sintering was 25 kN, the heating rate was 100 °C / min, the temperature reached 900 °C, and the holding time was 2 min; the pressure of the third sintering was 30 kN, the heating rate was 100 °C / min, the temperature reached 1350 °C, and the holding time was 3 min, and the vacuum degree was controlled to be ≤8×10 0 Pa, the pulse ratio of the sintering furnace is 14, and the heating voltage is 5~6V.

[0045] Comparative Example 1 The single crystal diamond is ultrasonically cleaned with anhydrous ethanol to remove and disperse the surface dirt to achieve the cleaning purpose, and then dried for use; Preparation of single crystal diamond composite material: According to the mass percentage, 70% of cleaned single crystal diamond, 10% TiC, 10% ZrH 2 and 10% Al were uniformly mixed using a planetary ball mill; the particle size of the single crystal diamond was 180 μm, the particle size of TiC was 10 μm, and the particle size of ZrH 2 The particle size of the raw material is 48 μm, and the particle size of the Al is 48 μm; vacuum ceramic jars and ceramic balls are used for ball milling, the ball milling speed is 180 rpm, the ball milling time is 48 h, and after uniform mixing, a single crystal diamond composite material is obtained, which is vacuum sealed for standby use; Preparation of cobalt-based ceramic composite materials: 5% of single crystal diamond composite materials, 70% of WC and 25% of Co were uniformly mixed by a planetary ball mill, wherein the particle size of WC powder was 48 μm, and the particle size of Co was 48 μm; the ball milling was carried out by using a vacuum stainless steel tank and stainless steel balls; the ball milling speed was 180 rpm, and the ball milling time was 48 h to obtain a mixture; The mixed material obtained above was evenly spread in a cylindrical graphite mold, placed in a sintering furnace, and the process parameters were adjusted to perform the first sintering, the second sintering and the third sintering in sequence to obtain a cobalt-based ceramic composite material; wherein the sintering parameters were as follows: the pressure of the first sintering was 12 kN, the heating rate was 80 °C / min, the temperature reached 600 °C, and the holding time was 2 min; the pressure of the second sintering was 25 kN, the heating rate was 80 °C / min, the temperature reached 900 °C, and the holding time was 2 min; the pressure of the third sintering was 30 kN, the heating rate was 80 °C / min, the temperature reached 1360 °C, and the holding time was 1.5 min, and the vacuum degree was controlled to be ≤8×10 0 Pa, the pulse ratio of the sintering furnace is 14, and the heating voltage is 5~6V.

[0046] Performance Testing Test Example 1 Figures 1 to 4 is a SEM image of the cobalt-based ceramic composite material obtained in Example 1, wherein Figure 1 The scale bar is 50 μm for the SEM images. Figure 2 The SEM image has a scale of 200 μm. Figure 3 The SEM image has a scale of 1 mm. Figure 4 The scale bar is 100 μm. Figures 1 to 4 It can be seen that the diamond is tightly bonded to the bonding phase, the bonding phase is evenly wrapped around the diamond, and the diamond and the matrix have a good transition.

[0047] Figure 5 The EDS spectrum of the cobalt-based ceramic composite material obtained in Example 1 is shown in FIG. Figure 5 It can be seen that diamond has not been carbonized and is tightly bonded to the bonding phase, and the bonding phase element composition is mainly Yb, W, Co, and Ti.

[0048] Figure 6-7 This is a SEM image of the cobalt-based ceramic composite material obtained in Example 2, wherein Figure 6 The scale bar is 100 μm for the SEM images. Figure 7 The scale bar is 20 μm. Figure 6-7 It can be seen that in the alloy composition obtained by the experimental scheme of Example 2, the matrix structure with a high particle size also has a good bonding effect on diamond.

[0049] Figure 8 The XRD pattern of the cobalt-based ceramic composite material obtained in Example 4 is shown in FIG. Figure 8 It can be seen that after sintering, new phases are generated (Al 0.5 W 0.5 C).

[0050] Figures 9-10The SEM images of the cobalt-based ceramic composite material obtained in Comparative Example 1 at different positions are shown in FIG. Fig. 9 and Fig.10 The scale bars are all 50 μm. Figures 9-10 It can be seen that after sintering using the process of Comparative Example 1, diamond is carbonized and the bonding is not dense, the alloy structure has a high porosity and the overall performance is poor.

[0051] Test Example 2 The wear resistance and average surface hardness of the cobalt-based ceramic composite materials obtained in Examples 1 to 4 and Comparative Example 1 were tested. The wear resistance test process was as follows: Si 3 N 4 The grinding ball was loaded with 100N, reciprocated at 500 times / min, and tested for 30min. After cleaning with anhydrous ethanol, the wear loss under dry friction was weighed. The test results are shown in Table 1. in, Fig.11 and Fig.12 is a three-dimensional profile diagram of the cobalt-based ceramic composite material obtained in Example 1 after the friction and wear test; Figures 11-12 It can be seen that the wear scar profile of Example 1 is relatively shallow, there is no obvious material adhesion around the wear scar, and the wear behavior during dry friction is mainly plastic deformation.

[0052] Table 1 Performance test results of cobalt-based ceramic composite materials obtained in Examples 1 to 4 and Comparative Example 1

[0053] According to Table 1, the hardness and wear resistance of Example 1 are much higher than those of the other three examples. Due to the different WC content and particle size of Example 1, the sintered ceramic tool material has a high density and a tighter bond. 2 O 3 , Yb 2 O 3 The addition of makes the hard phase more evenly distributed inside the alloy during sintering. The sintering parameter holding time is prolonged, so that more WC dissolves into the liquid phase when WC-Co is at the eutectic temperature during the sintering of cemented carbide. The increase in liquid phase process time produces more solid solution in the alloy structure, which strengthens the structure performance. However, it is necessary to prevent the grains from growing too large, reduce the total area of ​​the grain boundary in the crystal, and reduce the interface energy.

[0054] The present invention adopts TiC, ZrH 2 , Al coats the single crystal diamond, protecting the organizational properties of the diamond during sintering, while forming chemical bonds around the diamond, allowing a suitable transition between the diamond and the metal bonding phase. Figure 1As shown, the diamond is effectively and tightly bonded to the surrounding tissue, and the diamond has its original morphology and performance, which enhances the overall hardness and wear resistance. Figure 2 and Figure 7 , Fig.10 As shown in the comparison, the present invention adjusts the WC particle size, and the atoms are rearranged more closely during the sintering process, thereby improving the density of the organization. Fig.10 There are obvious intergranular cracks and gaps between the components. As one of the most important parameters of the process, the different holding time makes the reaction time of each component different during the sintering process. The different holding time at the eutectic temperature leads to different intermolecular bonding forces. Figure 1 and Figure 6 , Fig. 9 By comparison, it can be seen that the increase in holding time increases the grain growth and the diamond retention force. Fig. 9 Due to the short insulation time, the diamonds showed obvious shedding phenomenon.

[0055] Test Example 3 The electrochemical corrosion performance of the cobalt-based ceramic composite material obtained in Example 1 was tested; Step 1: Sample preparation: First, ultrasonically clean the sample using deionized water and anhydrous ethanol to remove surface oil and impurities. During the cleaning process, the frequency of the ultrasonic cleaner used was set to 40 kHz and the duration was 15 minutes. The cleaned sample was dried in clean air at a drying temperature of 60°C for 30 minutes, and then the sample was sealed for use.

[0056] Step 2: Preparation for electrochemical corrosion test: Electrochemical corrosion test was performed using a three-electrode system. The test electrolyte was a 5% NaCl solution. The prepared cobalt-based WC-diamond composite ceramic tool material sample was used as the working electrode, the platinum sheet was used as the counter electrode, and the calomel electrode was used as the reference electrode. The exposed area of ​​the working electrode was 1 cm² to ensure that the surface of the material sample was in full contact with the electrolyte. To reduce external interference, the entire test process was carried out in an electrochemical cell at room temperature (25°C), and the open circuit potential (OCP) was kept stable for 20 minutes before the corrosion test to ensure a stable electrochemical state.

[0057] Step 3: Polarization curve measurement: After the open circuit potential is stabilized, a dynamic potentiodynamic polarization curve test is performed. The potential scanning range starts from the open circuit potential (Eocp), scans in the range of ±1V, and the scanning rate is set to 0.5mV / s. By measuring the dynamic potentiodynamic polarization curve, the self-corrosion potential (Ecorr) and self-corrosion current density (Icorr) are calculated. According to the Tafel slope method, the anode slope (βa) and cathode slope (βc) are obtained by linear fitting of the anode and cathode regions of the polarization curve, and the polarization resistance (Rp) is calculated according to the Stern-Geary equation. Fig.13 This is the electrochemical polarization curve of the cobalt-based ceramic composite material obtained in Example 1.

[0058] Step 4: The self-corrosion potential (E corr =-0.614V) and self-corrosion current density (I corr =4.313×10 -6 A / cm 2 ). The low self-corrosion current density indicates a low corrosion rate, showing that the material has excellent corrosion resistance in corrosive media. The anodic branch of the polarization curve reflects the dissolution process of the Co-based binder phase, while the cathodic branch indicates the reduction behavior of dissolved oxygen on the material surface. The passivation film formed on the surface of the material effectively inhibits further corrosion progress, and the polarization resistance (Rp=35292 Ω·cm 2 The Tafel fitting method is used to calculate the self-corrosion potential (E corr ), self-corrosion current density (I corr ), anode Tafel constant (β a ) and the cathode Tafel constant (β c ). The polarization resistance Rp can be calculated by the Stern-Geary equation.

[0059]

[0060] Self-corrosion current density I corr The corrosion rate of the reaction material. The smaller the value, the slower the corrosion rate. corr ) is -0.614V, and the self-corrosion current density (I corr ) is 4.313×10 -6 A / cm 2 , polarization resistance (Rp) is 35292Ω·cm 2 It shows that the sample has good corrosion resistance.

[0061] in conclusion: The electrochemical polarization curve test shows that the cobalt-based ceramic composite material provided by the present invention has excellent electrochemical corrosion performance in 5% NaCl solution, showing high polarization resistance and low corrosion rate. Corrosion product analysis further verifies the corrosion resistance of the material, especially in the cobalt binding phase region. Although corrosion has a certain impact on the hardness and wear resistance of the material, the material still shows high mechanical properties and is suitable for use in highly corrosive environments.

[0062] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A single crystal diamond composite material, characterized in that: It comprises a single crystal diamond and a functional layer coated on the surface of the single crystal diamond; The materials of the functional layer include TiC, ZrH2 and Al.

2. The single crystal diamond composite material according to claim 1, characterized in that: The single crystal diamond composite material comprises the following components in percentage by mass: 50-60% single crystal diamond, 20-30% TiC, 5-15% ZrH2 and 5-15% Al; The particle size of the single crystal diamond is 100-200 μm; the particle size of the TiC is 0.5-10 μm; the particle size of the ZrH2 is 48-75 μm; and the particle size of the Al is 48-75 μm.

3. The method for preparing the single crystal diamond composite material according to claim 1 or 2, characterized in that: The following steps are involved: The components included in the single crystal diamond composite material are ball-milled and mixed to obtain the single crystal diamond composite material.

4. The preparation method according to claim 3, characterized in that: The ball milling mixing was performed at a rotation speed of 80-100 rpm for 48 h.

5. Use of the single crystal diamond composite material according to claim 1 or 2 or the single crystal diamond composite material prepared by the preparation method according to claim 3 or 4 in metal-ceramic composite materials.

6. A cobalt-based ceramic composite material, characterized in that: The preparation raw materials include the following mass percentages: WC 70-80%, Co 10-25%, Yb2O3 0-2% and the remainder modified diamond; The modified diamond is the single crystal diamond composite material according to claim 1 or 2 or the single crystal diamond composite material prepared by the preparation method according to claim 3 or 4.

7. The cobalt-based ceramic composite material according to claim 6, characterized in that: The particle size of the WC is 0.5-75 μm; The particle size of the Co is 48-75 μm; The particle size of the Yb2O3 is 48~75μm.

8. The method for preparing the cobalt-based ceramic composite material according to claim 6 or 7, characterized in that: The following steps are involved: Ball-milling and mixing the raw materials for preparing the cobalt-based ceramic composite material to obtain a mixed material; The mixed material is sintered to obtain the cobalt-based ceramic composite material.

9. The preparation method according to claim 8, characterized in that: The ball milling mixing is performed at a speed of 160-180 rpm for 48 hours; The sintering includes sequentially performing a first sintering, a second sintering and a third sintering; The first sintering temperature is 550-650°C, the holding time is 2-3 minutes, and the pressure is 12-15 kN; The second sintering temperature is 850-950°C, the holding time is 2-3 minutes, and the pressure is 23-25 ​​kN; The third sintering temperature is 1340-1360° C., the holding time is 0-6 min, and the pressure is 30-33 kN; The sintering is carried out under vacuum conditions, with a vacuum degree of ≤8×10 0 Pa.

10. Use of the cobalt-based ceramic composite material according to claim 6 or 7 or the cobalt-based ceramic composite material prepared by the preparation method according to claim 8 or 9 as a cutting tool.

Citation Information

Patent Citations

  • Nanoparticle composite welding filler materials, and methods for producing same

    CN110461535A

  • Laser cladding preparation method of ZrH2 reinforced cobalt-based diamond wear-resistant coating

    CN115786910A